Techno-Economic Analysis of Autotrophic Microalgae for Biofuel Production in India - Krishnan, Nithya Srinath (2013)
Modern society relies on non-renewable sources of energy which is the dominant source of energy, which accounts for nearly 84% of the overall increase in demand between 2005 and 2030 (Khan et al., 2009). The energy requirements are estimated to grow by 55% between 2005 and 2030, according to The International Energy Agency (2011). There is an increased demand for transportation of industrial and agricultural goods in India and more than three-quarters of the petroleum demands are met through imports (Khan et al., 2009). Exhaustion of the global petroleum reserve combined with the growing concern about environmental quality, particularly climate change has increased the search for alternate sources of energy. With the rapid increases in fossil fuel prices combined with the need for sustainable alternatives has brought microalgae as a source of biofuel back into the research and development (R&D) limelight. Microalgae as a feedstock for biofuel production are attractive as it is a source of clean and renewable energy. Unlike first generation crops, algae do not come into conflict with the food supply. The process of producing biodiesel from carbon neutral biomass can contribute significantly to the development of the rural economy by providing a non-polluting, biodegradable and safe environment (Khan et al., 2009). However, there are certain technical and economic challenges associated with the microalgae biofuel industry that limits the widespread use of this technology despite several efforts that have been made to solve these problems over the past several decades. For algae biofuels to substitute the fossil fuel industry and ensure sustainable and efficient energy production, distribution and use, a whole new set of technology-related materials and infrastructure needs to be set up to ensure that post-harvest losses are minimized with increased sustainability. The combination of generating energy from wastewater treatment along with a sustainable nutrient cycling addresses the reduction in greenhouse gas emission and the production of biofuels with long term sustainability. Providing long-term targets and supporting policies that stimulate investment in the production of algae biofuels can improve the economic situation. The main focus of this paper is to identify the challenges related to the sustainable production and commercialization of microalgae biofuel.